Fishery activity impact on the sotalia populations from the Amazon mouth - Beltran-Pedreros, Sandra; Petrere, Miguel [UNESP] (My University, 2010)
This chapter describes and analyzes the bycatch of Sotalia guianensis, in gillnets by an artisan fishing fleet within the Amazonian estuary during two time periods: 1996-1997 and 1999-2001. Number, size and gender data, as well as dolphin specimens were obtained from fishermen at Brazilian ports and analyzed. Fishing capacity and effort were determined via simple linear regression and bycatch, fishing trip and fishing effort data were analyzed between time-periods, among climatic (seasonal) periods and between strata (based on vessel length). Results indicated that the stratum two fishing fleet not only had larger vessels but longer fishing trips, used longer nets and had larger fishing crews compared to stratum one's fleet. Bycatch increased in both strata between periods but to a greater extent in stratum two. Although there was an increased percentage of fishing trips with bycatch across time, there was a reduced mean number of dolphins per bycatch. There were also differences in the bycatch by sexual maturity with an indiscriminately larger number of sexual-reproducing adults caught in stratum two. Collectively, these results in conjunction with other anthropogenic factors combined with dolphins being a k-selected species, suggest that dolphin mortality from bycatch may seriously affect Sotalia guianensis in the Amazonian estuary. Furthermore, the fishery-dolphin interaction was characterized and determined to be indirectly predatory. © 2010 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Amazonian estuary; Bycatch; Fishing-dolphin interaction.; Sotalia guianensis